Abc3-mediated efflux of an endogenous digoxin-like steroidal glycoside by Magnaporthe oryzae is necessary for host invasion during blast disease. - Rajesh N Patkar; Yang Kui Xue; Guanghou Shui; Markus R Wenk; Naweed I Naqvi (PLoS Pathogens, 2012)
Magnaporthe oryzae, which causes the devastating rice-blast disease, invades its host plants via a specialized infection structure called the appressorium. Previously, we showed that the ATP-Binding Cassette 3 transporter is necessary for appressorial function (host penetration) in M. oryzae. However, thus far, the molecular basis underlying impaired appressorial function in the abc3Δ remains elusive. We hypothesized that the abc3Δ appressoria accumulate excessive amounts of specific efflux substrate(s) of the Abc3 transporter in M. oryzae. We devised an innovative yeast-based strategy and identified Abc3 Transporter efflux Substrate (ATS) to be a digoxin-like endogenous steroidal glycoside that accumulates to inhibitory levels in M. oryzae abc3Δ appressoria. Exogenous ATS altered cell wall biogenesis and viability in wild-type Schizosaccharomyces pombe, but not in S. pombe expressing M. oryzae Abc3. We show that ATS associates with the Translation Elongation factor Tef2 in M. oryzae, and propose that ATS regulates ion homeostasis during pathogenesis. Excessive ATS accumulation, either intracellularly due to impaired efflux in the abc3Δ or when added exogenously to the wild type, renders M. oryzae nonpathogenic. Furthermore, we demonstrate that the host penetration defects in the abc3Δ are due to aberrant F-actin dynamics as a result of altered Tef2 function and/or ion homeostasis defects caused by excess accumulation of ATS therein. Rather surprisingly, excessive exogenous ATS or digoxin elicited the hypersensitive response in rice, even in the absence of the blast fungus. Lastly, reduced disease symptoms in the inoculated host plants in the presence of excessive digoxin suggest a potential use for such related steroidal glycosides in controlling rice-blast disease.